Hardware Integration and Real-Time Control in an Agent-Based Distribution Grid Simulation - Loose, Nils; Törsleff, Sebastian; Derksen, Christian; Unland, Rainer; Fay, Alexander (Advances in Practical Applications of Cyber-Physical Multi-Agent Systems: The PAAMS Collection, 2017)
In recent years, several developments in the energy sector have been imposing major challenges on our energy supply infrastructure. Due to the liberalization of the energy markets that started in the 1990s, longstanding monopolies are being broken up and new actors enter the stage. An increasing awareness regarding the environmental impacts of fossil fuel-based electricity generation put renewable energy sources like wind and solar on a lasting growth path. The volatility inherent to these sources and the shift from centralized to decentralized generation necessitate new approaches as to how energy is marketed, distributed and consumed. The smart grid, i.e. equipping the energy infrastructure with modern information and communication technology, is widely considered essential in addressing the challenges outlined.